2021
DOI: 10.33024/jikk.v8i3.4617
|View full text |Cite
|
Sign up to set email alerts
|

STUDI LITERATUR: PENGARUH PEMBERIAN EKSTRAK DAUN BAYAM MERAH (Amaranthus tricolor L.) TERHADAP INDEKS LEE DAN MASSA LEMAK ABDOMINAL PADA TIKUS PUTIH (Rattus norvegicus) GALUR WISTAR JANTAN YANG DIBERI DIET TINGGI LEMAK

Abstract: Obesitas didefinisikan sebagai akumulasi lemak yang tidak normal atau berlebihan yang dapat mengganggu kesehatan. Obesitas terjadi karena adanya peningkatan kolesterol plasma, Low-Density Lipoprotein (LDL), trigliserida dan penurunan kadar High Density Lipoprotein (HDL) atau kombinasi dari beberapa abnormalitas. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian ekstrak daun bayam merah (Amaranthus tricolor L.) terhadap indeks Lee dan massa lemak abdominal tubuh tikus putih wistar yang diinduksi diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Based on the results of this study can be concluded that administration of goroho banana peel extract can overcome oxidative stress thereby reducing body weight (Lee index), increasing the number of Leydig cells, and increasing testosterone levels in male Wistar rats with obesity. The results of this study are in line with research conducted by Rusmini et al, that administration of several extracts from plants containing antioxidant compounds such as flavonoids, tannins, saponins, phenolics, alkaloids, menoterpenes, sesquiterpenes, quinones can reduce Lee's obesity index by 4.46% -11.94% (Rusmini et al, 2021).…”
Section: Administration Of Goroho Banana Peel Extract (Musa Acuminata...supporting
confidence: 92%
See 1 more Smart Citation
“…Based on the results of this study can be concluded that administration of goroho banana peel extract can overcome oxidative stress thereby reducing body weight (Lee index), increasing the number of Leydig cells, and increasing testosterone levels in male Wistar rats with obesity. The results of this study are in line with research conducted by Rusmini et al, that administration of several extracts from plants containing antioxidant compounds such as flavonoids, tannins, saponins, phenolics, alkaloids, menoterpenes, sesquiterpenes, quinones can reduce Lee's obesity index by 4.46% -11.94% (Rusmini et al, 2021).…”
Section: Administration Of Goroho Banana Peel Extract (Musa Acuminata...supporting
confidence: 92%
“…According to study from Rusmini et al, administration of plant extracts that contain antioxidants, namely flavonoids, tannins, saponins, phenolics, alkaloids, menoterpenes, sesquiterpenes, quinones can reduce Lee's obesity index by 4.46% -11.94% (Rusmini et al, 2021). The dose of ethanol extract of 6.3 g/kg BW of goroho banana peel used in this study was based on previous studies because it contains secondary metabolic compounds of flavonoids, saponins, tannins as antioxidants which have been shown to be effective in significantly reducing blood glucose in male Wistar rats (Syamsuddin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tannin compounds play a role in preventing obesity by reducing body mass and fat, whereas tannin compounds play a role in contracting the intestine so that peristalsis is reduced [32]. tannins have an inhibitory mechanism of pancreatic lipase enzymes so that less fat is absorbed by the body [33]. In addition, tannins function in inhibiting fat absorption in the intestinal organs, namely by the reaction between mucosal proteins and intestinal epithelial cells, so that fat levels that cause obesity can decrease.…”
Section: Figure 2 Total Cholesterol Level Of High Fat Diet-induced Ob...mentioning
confidence: 99%
“…In addition to flavonoids, tannins, and alkaloids, saponin compounds also play a role in antiobesity activity, losing weight by inhibiting pancreatic lipase activity that binds to cholesterol. Saponins will enter the gastrointestinal tract and are not absorbed by the digestive tract so that saponins bound to cholesterol can come out of the gastrointestinal tract [33]. Secondary metabolite compounds in C. hirta leaves reduce body weight and total cholesterol levels of obese mice.…”
Section: Figure 2 Total Cholesterol Level Of High Fat Diet-induced Ob...mentioning
confidence: 99%